O que os cidadãos cientistas informam sobre os crocodilianos? - Souza, Maryana Tavares de (2023)
The effective conservation of crocodilians needs to be addressed through partnerships such as crocodilian conservation projects, alliances between conservationists and citizen scientists. Citizen science is an effective tool in expanding scientific knowledge because it may engage more people and on a larger scale than scientists can collect data. In the present study, we compiled data of crocodilians recorded by citizen scientists from the iNaturalist platform on a global scale. We also evaluated the number of observations of crocodilians across families, genera, and species, their geographic distribution and the number of observations and users of iNaturalist over time. Our final dataset had 65,014 observations from 22,753 observers, representing 27 species of crocodilians from nine genera and three families. Alligator mississippiensis (41,083 observations; 63%) and Crocodylus acutus (6,400 observations; 10%) had the highest number of observations. Regarding conservation status, 11 (41%) 10 species are threatened to extinction on the IUCN Red List (IUCN, 2023), of which seven (26%) are Critically Endangered (CR) and four (15%) Vulnerable (VU). The final dataset included observations from 100 countries. USA (N = 41,954; 65%) had the highest number of observations and Brazil (N = 6 species; 22%) and Colombia (N = 6 species; 22%) had the highest number of species. The number of observations increased significantly in 2016 (2,479), and reached a mean of 8,843 observations per year until 2022. Due to the Covid-19 pandemia, there was a decrease in the number of observations (8,118) in 2020. It is therefore concluded that the study covering data from citizen scientists provides valuable data regarding the spatial and temporal distribution of crocodilians on a global scale. Therefore, the use of iNaturalist is a useful tool to complement scientific data, favoring research and conservation efforts for crocodilians around the world.